2012
DOI: 10.1111/1471-0528.12014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a counselling intervention on weight changes during and after pregnancy: a randomised trial

Abstract: Objectives To evaluate the effects of a counselling intervention on excessive weight gain during pregnancy and postpartum weight retention.Design The New Life(style) study was a randomised trial with a control group (n = 113) and an intervention group (n = 106).Setting Midwife practices in the Netherlands.Population Women with a healthy pregnancy, expecting their first baby.Methods The intervention consisted of four face-to-face counselling sessions about weight, physical activity and diet during pregnancy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
139
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(145 citation statements)
references
References 33 publications
2
139
1
3
Order By: Relevance
“…We identified 58 trials published up to June 2015, of which 36 studies (62%) provided individual participant data (IPD),1617343536373839404142434445464748495051525354555657585960616263646566 that accounted for data from 80% of the participants (12 526/15 541); 22 studies (3015 women) did not provide IPD (fig 1). 67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 58 trials published up to June 2015, of which 36 studies (62%) provided individual participant data (IPD),1617343536373839404142434445464748495051525354555657585960616263646566 that accounted for data from 80% of the participants (12 526/15 541); 22 studies (3015 women) did not provide IPD (fig 1). 67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122…”
Section: Resultsmentioning
confidence: 99%
“…Twenty two studies17343637383941424748515253565758596061626367 were from Europe, four each from North America,44546566 Australia,16434550 and Brazil,35495564 and one study each from Egypt40 and Iran 46. Twenty three IPD studies included women of any body mass index (BMI),3435363738424445464748525455565859606164656667 seven included only obese women,17394041506263 and six included obese and overweight women 164349515357. The interventions included those mainly based on diet (four IPD studies)47616264 or physical activity (16 IPD studies),3536374246495051525558596566…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the study by Althuizen et al 56 showed that prenatal exercise + co-intervention (diet and behavioural intervention) did not reduce the odds of retaining >5 kg at 12 months postpartum (OR 1.2, 95% CI 0.41 to 3.51). Similarly, Phelan et al reported no effect of prenatal exercise + co-intervention (diet and behavioural intervention) on the odds of returning to pre-pregnancy weight at 12 months postpartum (OR 1.6, 95% CI 0.92 to 2.7) 72.…”
Section: Resultsmentioning
confidence: 99%
“…Las unidades de análisis según el ámbito geográfico de procedencia muestran un predominio de investigaciones provenientes de Asia (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) seguidas por las experiencias de América del Norte (24-34), Europa (35)(36)(37)(38)(39)(40)(41)(42), América Latina (43-49) y en menor medida las procedentes de Oceanía (50-51) y África (52-53).…”
Section: Resultsunclassified